Analisis Fungsi Kepala Ruang Menurut Perspektif Staf Keperawatan Di Rsjdsurakarta - Afrizal, Afrizal, Arum Pratiwi, S.Kp., M.Kes, Vinami Yulian, S.Kep., Ns., M.Sc (2016)
Head Office directly responsible ensuring activities within the organization. In institutes of nursing services, each manager on duty to ensure that entire intended purpose by the nursing can be realized through a series of management activities, both functionally and operationally. Management functions divided into four functions such as ning,organizing, aiming and monitoring. Purpose of research to determine function of Head Office according the perspective of nursing staff. Research include descriptive. Population of research include nursing staff at RSJD Surakarta district with sample of 68 respondents. Variables of research are the function of Head Office. Data were analyzed using frequency distribution and standard deviation. Results showed that according to nursing staff in RSJD, Head Office has operate properly. So expect to Head Office stay operate properly in accordance with a job description and operational standards. Keywords: Function Of Head Office , Nursing Staff